Seni Tari dalam Mengembangkan Kemampuan Sosial Emosional Anak Usia Dini - Ade Karunia Rizky Manurung; Eka Lestari; Widya Firdausi Lasty (Lembaga Teewan Journal Solutions, 2026)
Dance art is one of the most effective creative learning media in supporting the social-emotional development of early childhood. This study aims to analyze the role of dance art activities in developing the social-emotional abilities of children aged 4-6 years in early childhood education institutions. This research uses a qualitative approach with a case study design conducted at three kindergartens in Medan City. Data were collected through observation, in-depth interviews with teachers and parents, and documentation. The results of the study show that dance art activities significantly contribute to the development of children's social-emotional abilities, including the ability to manage emotions, cooperate, empathize, and build positive relationships with peers. Children who regularly participate in dance activities show better social interaction patterns and emotional stability compared to those who do not participate. The implication of this research is that dance art learning should be integrated as a core component in early childhood education curricula to support holistic character development..